EFL Teachers’ Strategies for Overcoming Speaking Barriers in Class X MAN 8 Jombang - Ali, Indi Aulia; Kurniawan, Andri; Suwandi (Lembaga Pengembangan Bahasa Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This study investigates the methods used by English as a Foreign Language (EFL) instructors to help Class 10 students at MAN 8 Jombang overcome speaking obstacles. Finding efficient teaching strategies that can improve students' speaking abilities which are essential for communicative competence in a foreign language is the main goal. Through documentation, interviews, and observations, data was gathered using a qualitative descriptive research methodology. According to the findings, teachers greatly increased their students' confidence and fluency in speaking English by implementing techniques like role-plays, debates, and storytelling to create an engaging classroom environment. Additionally, managing students' fears and increasing their motivation required the use of strategies like scaffolding and tailored feedback.